Chemdex: In Search of a Viable Business Model - Meyer, Marc; de Crescenzo, Neil; Russell, Bruce (Senate Hall, 2004)
The case uses the dramatic rise and fall of a Web-economy company from 1997 to 2002 to help students consider the meaning and design of business models. The company, formerly known as Chemdex, and then Ventro, is now known as Nexprise. Once traded on NASDAQ at a share price of $250 and a valuation of approximately $8 billion, today the stock is traded on the OTC exchange for about $1 per share and a market capitalization of less than $5 million. The case describes the four business strategies and three distinct business models embraced by the company over the past five years.
Keywords: business model|venture finance|company valuation|internet bubble|and business planning